Associations of Army Fathers' PTSD Symptoms and Child Functioning: Within‐ and Between‐Family Effects. Issue 4 (25th March 2018) - Parsons, Aleja; Knopp, Kayla; Rhoades, Galena K.; Allen, Elizabeth S.; Markman, Howard J.; Stanley, Scott M.
Abstract : This study examined the within‐family and between‐family associations between fathers' military‐related PTSD symptoms and parent ratings of children's behavioral and emotional problems. The sample included married couples ( N = 419) with children composed of a civilian wife and an active‐duty husband serving in the U.S. Army. Results indicate that changes in fathers' PTSD symptoms over time were associated with corresponding changes in both mothers' and fathers' reports of child behavioral and emotional problems. These within‐family findings were independent from between‐family effects, which showed that higher average PTSD symptomatology was associated with more overall behavioral and emotional problems for children. This study uses advances in statistical methodologies to increase knowledge about how PTSD symptoms and child problems are related, both across different families and over time within families.